Design and Cloning of Gene Encoding SLPI C-Terminal Domain in Escherichia coli TOP10 - Evi Umayah Ulfa; Ni Nyoman Tri Puspaningsih (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Elevated levels of neutrophil elastase in CPOD (Chronic Obstructive Pulmonary Disease) airways are regarded as the main trigger of lung destruction and inflammation. SLPI (Secretory leukocyte protease inhibitor), an inhibitor protease, represents an attractive candidate for treatment in chronic lung diseases due to proteases excess. The antiprotease active site of SLPI has been located on the C-terminal domain. This study aimed to design and clone the gene encoding the C-terminal domain of SLPI (SLPIc). The gene encoding SLPIc was optimized and predicted solubility using OptimumGene™ and SoDoPe software. The nucleotide sequence of the optimized SLPIc was synthesized, inserted into the pGEX 4T-2 vector commercially by Genscript, and transformed into the Escherichia coli TOP10. The pGEX 4T-2 vector contains a glutathione S transferase (GST) gene located before the MCS to generate a recombinant protein for fusion with GST. For purification purposes, the His-tag synthesized together with SLPIc. The optimized SLPIc nucleotide sequence gave a CAI value of 0.81, GC content 52.31, and a CFD of 2%. The solubility probability of SLPI fused with GST increased from 0.124 to 0.4656. Confirmation of the transformant using restriction and sequencing analysis showed that the gene encoding of SLPI domain C-terminal optimized in the pGEX 4T-2 plasmid was successfully transformed into E. coli TOP10 as novelty of this study. The optimized SLPIc gene in pGEX 4T-2 has a high probability of being expressed in E. coli based on in-silico analysis.